Development of Squat-and-Smile Test as Proxy for Femoral Shaft Fracture-Healing in Patients in Dar es Salaam, Tanzania. (20th February 2019) - Wu, Hao-Hua; Liu, Max; Challa, Sravya T.; Morshed, Saam; Eliezer, E.N.; Haonga, Billy T.; Zirkle, Lewis; Shearer, David W.
Abstract : Background: There are few validated instruments that serve as a proxy for fracture-healing after lower-extremity trauma in low-resource settings. The squat-and-smile test (S&S) has been under development by SIGN (Surgical Implant Generation Network) Fracture Care International to monitor outcomes of lower-extremity long-bone fractures after intramedullary nailing in resource-limited settings. The goals of this study were to develop and identify domains of the S&S test. Methods: The S&S domains were developed through an iterative process, and consensus was achieved regarding 3: squat depth, support needed to squat, and facial expression. Adult patients with an OTA/AO type-32 femoral shaft fracture were included in this retrospective study and had the S&S administered at 6 weeks and 3, 6, and 12 months postoperatively. Two authors independently assessed photographs of the patients performing the S&S. S&S domains were correlated with the EuroQol 5-Dimensions (EQ-5D) index score, and comparisons were made between S&S domains and reoperation status. Interrater and test-retest reliability was assessed using the kappa statistic. Sensitivity and specificity analyses were performed. Results: Six hundred and nine S&S images were evaluated for 231 patients. Each domain improved over time and correlated positively with EQ-5D scores (p < 0.05). Squat depth and support needed to squat correlated with the need for a reoperation (p ⩽ 0.01), and both had high specificity (0.95 and 0.97, respectively) for ruling out the need for a reoperation at 1 year. All 3 domains had high test-retest reliability (κ = 0.95, 0.92, and 0.96). Squat depth and need for support also had strong interrater reliability (κ = 0.75 and 0.78). Conclusions: The S&S is a potential tool for monitoring clinical and functional outcome of femoral shaft fractures in low-resource settings. Our data support the binary assessment of squat depth and need for support, but not facial expression, as a proxy for fracture-healing. Future prospective studies in external populations are warranted to evaluate the validity, reliability, and responsiveness of the S&S. Clinical Relevance: The S&S provides a valuable proxy for femoral shaft fracture assessment for middle to low-income countries because it is locally relevant (based on squatting), it is easy to administer, and assessment can be performed remotely via mobile telephone or text messaging.